ANALISIS KINERJA PROSES DAN PRODUK DENGAN PENDEKATAN METODOLOGI SIX SIGMA (DMAIC) UNTUK PRODUK TEH BOTOL PADA PT XYZ - Hartono, Gunawarman; Putro, Tri Nugroho; Farhan, Ferdy; Fitrianingtyas, Rizky (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
PT XYZ is the pioneer company in Indonesia and the World which produces bottled tea beverage products. The company always strives to improve quality, especially in minimizing nonstandard products that occur in every process of production. Therefore the company needs corrective action to reduce the variations of non-standard products that occur on each process. In this study, the author uses Six Sigma methodology with an improvement model Define-Measure-Analyze-Improve-Control (DMAIC) to analyze process and product performance bottled tea at PT XYZ. By applying this methodology, the process and product performance of the company expected to increase and reach the higher level of sigma.